2014
DOI: 10.1002/2014gl059860
|View full text |Cite
|
Sign up to set email alerts
|

A multi tracer analysis of thermosphere to stratosphere descent triggered by the 2013 Stratospheric Sudden Warming

Abstract: Arctic winter observations in 2013 by the Solar Occultation for Ice Experiment (SOFIE) show significant transport from the lower-thermosphere to the stratosphere of air enriched in nitric oxide, but depleted in water and methane. The transport is triggered by the Stratospheric Sudden Warming (SSW) on 11 January and is continuously tracked for over 3 months. Ultimately, evidence for lower thermospheric air is seen at 40 km in mid-April. Area integrated nitric oxide (NO) fluxes are compared with previous events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 39 publications
4
76
0
Order By: Relevance
“…The importance of the residual circulation for the formation of the new elevated stratopause is also confirmed by several studies that observe enhanced transport of trace species from the mesosphere downward, induced by an enhanced poleward and downward-directed residual circulation (e.g., Manney et al, 2009a, b;Orsolini et al, 2010;Salmi et al, 2013;Bailey et al, 2014).…”
Section: Discussion Of Gravity Wave Potential Dragmentioning
confidence: 58%
“…The importance of the residual circulation for the formation of the new elevated stratopause is also confirmed by several studies that observe enhanced transport of trace species from the mesosphere downward, induced by an enhanced poleward and downward-directed residual circulation (e.g., Manney et al, 2009a, b;Orsolini et al, 2010;Salmi et al, 2013;Bailey et al, 2014).…”
Section: Discussion Of Gravity Wave Potential Dragmentioning
confidence: 58%
“…This gives an 11-day running mean of the rate of vertical motion. The calculation can be done for multiple VMRs, to retrieve a vertical profile of the rates of vertical motion, as in Bailey et al (2014). The term used here to denote the rate of vertical motion calculated using CO VMR is w CO , following Hoffmann (2012 here includes information on changes in CO VMRs due to all terms of the continuity equation in Sect.…”
Section: Rates Of Vertical Motion With Sd-waccm Comentioning
confidence: 99%
“…Straub et al, 2012) but a varying vertical gradient limits the altitudes at which it can be used (Lee et al, 2011). Nassar et al (2005) used nitrous oxide (N 2 O), CH 4 , and H 2 O to infer rates of vertical motion in the upper stratosphere and lower mesosphere, and Bailey et al (2014) used a combination of NO, H 2 O, and CH 4 to derive profiles of vertical motion in the middle atmosphere. A partial list of studies that have used tracers to calculate rates of vertical motion is given in Table 1, similar to Hoffmann (2012) for studies using CO.…”
Section: Introductionmentioning
confidence: 99%
“…During the recovery phase of these extended events, the anomalous zonal wind flow alters the gravity wave propagation to the mesosphere, thus perturbing the mean meridional circulation and driving a dramatic de-7958 D. E. Siskind et al: Summer stratospheric CH 4 scent of mesospheric air down to the stratosphere (Siskind et al, 2010;Chandran et al, 2013). For example, (Bailey et al, 2014) have shown that mesospheric air enhanced in nitric oxide (NO) and depleted in water vapor (H 2 O) and methane (CH 4 ) can descend from near 90 km in early February down to 40 km by early April. Bailey et al (2014) focused on the 2013 SSW; other analogous events occurred in 2004Randall et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, (Bailey et al, 2014) have shown that mesospheric air enhanced in nitric oxide (NO) and depleted in water vapor (H 2 O) and methane (CH 4 ) can descend from near 90 km in early February down to 40 km by early April. Bailey et al (2014) focused on the 2013 SSW; other analogous events occurred in 2004Randall et al, 2009). An additional motivation for most of the above studies is the interest in quantifying the extent to which the enhanced nitric oxide can cause reductions in polar upper stratospheric ozone (Funke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%